Analysis of The Causes of Project Delays Ceramic Finishing Work With Importance Index Method to Improve Time Performance - Tri Wahidi; Yopi Lutfiansyah; Elhazri Hasdian; Novika Candra Fertili (Journal of World Conference (JWC), 2021)
UrbanTown Serpong is an integrated vertical residential area developed in the buffer zone of the capital city, business and industrial center, and connected to mass transportation facilities. Which carries the concept of integrated entrepreneurship with many supporting facilities. However, not all construction projects can be completed on schedule. There are several delay factors that can occur, such as caused by time estimation; improper management; material problems; labor; equipment; finance; and an unsupportive environment. This study aims to determine the dominant factors that cause delays during construction and solutions to prevent delays in the development of the UrbanTown - Serpong Project. The factor analysis uses the Importance Index (IMPI) method to assess which factors are classified as high in the project. The results of the study indicate that there are 4 out of 31 indicators that have a significant effect on the factors causing work delays, including: constrained by labor shortages; the work is not carried out with the correct method; lack of material; and owner delays in making decisions.